Correlation Between Drinking Coffee and Incident Hypertension in Maospati Magetan District - Hamidatus Daris Sa’adah; Devy Naning Kurniasari; Yudisa Diaz Lutfi Sandi; Sandi Alfa Wiga Arsa (Journal of Ners and Midwifery, 2022)
Hypertension is a common disease in primary care. Hypertension is a cardiovascular disorder marked by elevated blood pressure caused by coffee consumption. Coffee is favorite common drink in Indonesia, is one of the causes of hypertension. This study aims to analyze the relationship between consumtion coffee habits and the incidence of hypertension in the Tanjungsepreh village. The study use cross sectional approch and collected data research were obtained by partitipan filling out a questionnaire. univariate analysis used descriptive statistics and bivariate analysis using the Spearman-rank test. In this study, there were 36 respondents with significant results, P-value = 0.039 and α = 0.05, which means that there is a relationship between consumption coffee habits and the hypertension for humans.